Mesenchymal stromal cells ameliorate diabetes‐induced muscle atrophy through exosomes by enhancing AMPK/ULK1‐mediated autophagy. Issue 2 (27th January 2023) - Song, Jia; Liu, Jidong; Cui, Chen; Hu, Huiqing; Zang, Nan; Yang, Mengmeng; Yang, Jingwen; Zou, Ying; Li, Jinquan; Wang, Lingshu; He, Qin; Guo, Xinghong; et al.
Abstract: Background: Diabetes and obesity are associated with muscle atrophy that reduces life quality and lacks effective treatment. Mesenchymal stromal cell (MSC)‐based therapy can ameliorate high fat‐diet (HFD) and immobilization (IM)‐induced muscle atrophy in mice. However, the effect of MSCs on muscle atrophy in type 2 diabetes mellitus (T2DM) and the potential mechanism is unclear. Here, we evaluated the efficacy and explored molecular mechanisms of human umbilical cord MSCs (hucMSCs) and hucMSC‐derived exosomes (MSC‐EXO) on diabetes‐ and obesity‐induced muscle atrophy. Methods: Diabetic db/db mice, mice fed with high‐fat diet (HFD), mice with hindlimb immobilization (IM), and C2C12 myotubes were used to explore the effect of hucMSCs or MSC‐EXO in alleviating muscle atrophy. Grip strength test and treadmill running were used to measure skeletal muscle strength and performance. Body composition, muscle weight, and muscle fibre cross‐sectional area (CSA) was used to evaluate muscle mass. RNA‐seq analysis of tibialis anterior (TA) muscle and Western blot analysis of muscle atrophy signalling, including MuRF1 and Atrogin 1, were performed to investigate the underlying mechanisms. Results: hucMSCs increased grip strength ( P  = 0.0256 in db/db mice, P  = 0.012 in HFD mice, P  = 0.0097 in IM mice), running endurance ( P  = 0.0154 in HFD mice, P  = 0.0006 in IM mice), and muscle mass ( P  = 0.0004 in db/db mice, P  = 0.0076 in HFD mice, P  = 0.0144 in IM mice) in all models tested, with elevated CSA of muscle fibres ( P  < 0.0001 in db/db mice and HFD mice, P  = 0.0088 in IM mice) and reduced Atrogin1 ( P  = 0.0459 in db/db mice, P  = 0.0088 in HFD mice, P  = 0.0016 in IM mice) and MuRF1 expression ( P  = 0.0004 in db/db mice, P  = 0.0077 in HFD mice, P  = 0.0451 in IM mice). MSC‐EXO replicated all these hucMSC‐mediated changes ( P  = 0.0103 for grip strength, P  = 0.013 for muscle mass, P  < 0.0001 for CSA of muscle fibres, P  = 0.0171 for Atrogin1 expression, and P  = 0.006 for MuRF1 expression). RNA‐seq revealed that hucMSCs activated the AMPK/ULK1 signalling and enhanced autophagy. Knockdown of AMPK or inhibition of autophagy with 3‐methyladenine (3‐MA) diminished the beneficial anti‐atrophy effects of hucMSCs or MSC‐EXO. Conclusions: Our results suggest that human umbilical cord mesenchymal stromal cells mitigate diabetes‐ and obesity‐induced muscle atrophy via enhancing AMPK/ULK1‐mediated autophagy through exosomes, with implications of applying hucMSCs or hucMSC‐derived exosomes to treat muscle atrophy.